Komunitas Online dan Penggerak Dakwah: Studi Tentang Saluran Whatsapp Ustaz Hanan Attaki dalam Menyebarkan Pesan Keagamaan - Rosyida, Ela; Shodiqoh, Mira (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2025)
Da'wah refers to the effort in Islam to convey Islamic teachings and values to others, inviting them toward goodness, truth, and a path approved by Allah. It goes beyond just sharing religious information; it also involves guiding others in their spiritual, social, and moral lives. In today's digital age, preachers can reach audiences from all corners of the world using platforms like YouTube, Instagram, Facebook, WhatsApp, and more. Ustadz Hanan Attaki, a popular young preacher known for his modern and flexible style, has gained significant attention, especially among teenagers. Moreover, WhatsApp's channel creation feature provides an opportunity for da'wah activists to build online communities, allowing them to reach a broader audience, particularly the youth who are heavily engaged in cyberspace. This research aims to analyze the spread of religious messages through digital media, particularly on WhatsApp channels, and evaluate the effectiveness of social media in fostering religious communities. A qualitative approach, using a case study method, was employed to examine the role of WhatsApp channels in spreading religious messages. Data was collected through observations on WhatsApp channels to understand interaction dynamics, content management, and communication effectiveness in reaching followers, as well as through interviews with followers of the channel.